Pelatihan Public Speaking di Desa Rongdurin Tanah Merah Bangkalan - Shonhaji Shonhaji; Ahmad Bahrudin; M. Thohir (Jurnal Kabar Masyarakat, 2023)
Basically, everyone has the ability to speak but not everyone is able to speak communicatively and attractively in public. Public speaking is a skill or ability or one that can be learned. The technique can be easily learned and has become a common thing that can be done by many people, because nowadays public speaking is one of the most challenging things in personal, social and professional life. For some people, being able to speak in public is a scary thing. This can happen to anyone, whether they are still in school, college, or those who are already working and have a family. Feelings of fear and awkwardness often arise when we see that there are many people who are ready to pay attention to us. In fact, public speaking is very important and needed by everyone in various aspects of life. Of course, to overcome this requires the ability to communicate effectively and on target. Thus the following are the basics and tips of Public Speaking. In general, Public Speaking is speaking in public or speaking in front of the public, which is an action, action or skill of speaking to a large group of people or the art of communicating orally which is carried out by someone to a group of people directly face to face. Examples include speeches, moderators, and presentations. Public speaking is a more special skill than just speaking with other people. Public speaking requires more than just preparation talk because of its nature which aims to communicate about a topic in before many people to influence, invite, change opinions, and give information. Therefore holding a training on public speaking for children and youth, so that they know the importance of having public speaking skills and improve those skills. This program is carried out by the method of providing material, roleplay, games and training. This kind of training is very important, especially when have been involved in the community will be much needed in the future, then education about public speaking needs to be known early on.